Are you listening? The relevance of what pastoral/denominational leaders and theological educators are saying about preparing leaders for ministry. Issue 4 (8th August 2019) - Wong, Arch Chee Keen; McAlpine, Bill; Thiessen, Joel; Walker, Keith
ABSTRACT: What might pastoral leaders in flourishing congregations have to say to theological educators in preparing leaders for the church and visa-versa? Drawing on interviews and focus groups with over one hundred pastoral/denominational leaders across Canada, four key themes emerged: (1) Equipping the Saints; (2) Practical Discipleship Training; (3) Spiritual Formation of seminary students; and (4) Missional and Organizational Training. The article contains several ways that pastoral leaders and theological educators might move forward with these findings.